Long-Term Follow-Up of Intrastromal Corneal Ring Segments in Paracentral Keratoconus with Coincident Corneal Keratometric, Comatic, and Refractive Axes: Stability of the Procedure - Luis Fernández-Vega Cueto; Carlos Lisa; David Madrid-Costa; Jesús Merayo-Lloves; José F. Alfonso (Journal of Ophthalmology)
Purpose. To assess the long-term outcomes of implanting intrastromal corneal ring segments (ICRS) in paracentral keratoconic eyes. Methods. 58 eyes with paracentral keratoconus with coincident refractive, keratometric, and comatic axes were evaluated. Uncorrected (UDVA) and corrected (CDVA) distance visual acuity and refractive errors were recorded before and at all follow-up visits. The postoperative follow-up was 5 years. Patients were divided into two groups: group I (30 years old or younger) and group II (more than 30 years old). Results. The mean UDVA (logMAR) rose from a preoperative 0.83 ± 0.31 to a five-year postoperative 0.42 ± 0.33 (P<0.0001). The mean CDVA varied from 0.16 ± 0.17 to 0.11 ± 0.18 (P=0.0003). Both the UDVA and CDVA were stable over the postoperative period in both groups (P>0.05). The spherical equivalent and the refractive cylinder declined steeply after ICRS implantation in both groups (P<0.001), and were stable over the postoperative period (P>0.05). The keratometric values were also stable over the postoperative follow-up. Conclusion. Ferrara-type ICRS implantation in keratoconus that meets the characteristics of the sample under study reduces the refractive error at the same time as it improves postoperative UDVA and CDVA six months after surgery and that these results remain stable over five years of follow-up.